Needs Needs Analysis of Discovery Learning Model in Physics Learning for Students - Rumsariadi, Rio Fahlevi; Sari, Silvi Yulia; Hufri, Hufri; Dewi, Wahyuni Satria (Department of Physics Universitas Negeri Padang, 2023)
Education is a basic need that must be done by every human being. In education, the Discovery Learning model is one of the innovative and appropriate models used in physics learning because this model prioritizes student discovery of the knowledge gained. The identification of problems expressed include: 1) The application of the learning model is not yet fully perfect; 2) Some students do not provide feedback to the teacher who teaches; 3) Student learning outcomes are still fairly low; 4) Student errors in understanding physics material; 5) The mechanics material used is momentum and impulse, and simple harmonic vibrations. Furthermore, the problem limitations used include: 1) Some students do not give feedback to the teacher; 2) Student learning outcomes are still fairly low; 3) The mechanics material used is momentum and impulse, and simple harmonic vibrations. This type of research is descriptive research that aims to determine the needs of the discovery learning model in the school under study. The research instrument was made with a questionnaire addressed to 2 physics teachers and students of class X Natural Science 1 - X Natural Science 6, an interview sheet addressed to 2 physics teachers. The data obtained that the discovery learning model has been applied and to determine the need for discovery learning models in learning, it is analyzed through student responses and teacher readiness with existing facilities and infrastructure. The advantages are effective to increase student activeness and the weaknesses are not all physics material that can be applied with the learning model, some students are still passive, limited time and student understanding is still low.